Study on the Process and Mechanism of Slope Failure Induced by Mining under Open Pit Slope: A Case Study from Yanqianshan Iron Mine, China - Yingpeng Hu; Fengyu Ren; Hangxing Ding; Yu Fu; Baohui Tan (Advances in Civil Engineering)
Mining under an open pit slope results in the collapse and slide of the slope. In this paper, a combination of methods including Google Earth and field investigations is applied to investigate the process of eastern slope failure induced by underground mining in the Yanqianshan Iron Mine over five years. According to the observed ground deformation features, the geomorphic zone of the eastern slope can be divided into four regions (caved rock zone, cracking zone, toppling zone, and sliding zone). Break angles and fracture initiation angles at different times are counted separately. Based on the above work, the process of initiation and development of slope failure is studied. The analysis results show that the process of slope failure could be chronologically divided into three stages. First, a collapse pit, caused by the falling of the overlying strata above the goaf, appeared on the eastern slope. Then, the rock mass around the collapse pit slid into the pit to form a small landslide. Finally, because of mining disturbances and rock creep, a large landslide occurred on the northeastern phyllite slope. The control mechanisms of each failure stage are discussed separately. Finally, the RFPA3D code is employed to simulate the slope failure process under the influence of underground mining. The results are consistent with the field observations, which provided information on deformation failure and the mechanics of the slope that could not be directly observed in the field and deepened the mechanism analysis.